Generating programming exercises with changeable complexity and level of abstraction - Tiam-Lee, Thomas James Z. (Animo Repository, 2018)
We present an approach for automatically generating coding exercises with varying complexity and level of abstraction. Using our approach, we can produce exercises based on abstract computational operations which are useful for learning the syntax of a programming language, as well as exercises based on real-life contexts which are useful for learning abstraction and logic formulation. We present the details of our approach as well as an initial evaluation of the exercises produced by students and teachers of programming. Our work can pave the way for the development of intelligent programming tutors with adaptive feedback that can display content based on the state of the student.